A Circumcision Method in an Old Surgical Textbook (Cerrahiyyetul Haniyye): Reminding of a Forgotten Procedure - Senayli, Atilla; Aksu, Murat; Atalar, Munir (Urology Journal, 2014)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --><!--[endif] -->Purpose: Circumcision is one of the historical surgical procedures. Some sources throughout the history contain various definitions about different circumcision methods. we described the details of the method, and aimed to remind the possibility of contemporary usage. Materials and Methods: We compared circumcision chapters of Sabuncuoglu and Zahrawi to explain the historical origin of Sabuncuoglu's favorite circumcision method. Results: We found a method which might be summarized as "knotting with rope technique" in one of historical textbooks named as Cerrahiyyetul Haniyye (Imperial Surgery) written by Serefeddin Sabuncuoglu (1385-1468?) in 1465. Conclusion: This circumcision method is not used currently. In addition this method has not been defined in the history of medical literature yet. <!--EndFragment-->